Knowledge of General Dental Practitioners and Specialists about Emergency Management of Traumatic Dental Injuries in Qassim, Saudi Arabia - Sanaa N. Al-Haj Ali; Somaya A. Algarawi; Atheer M. Alrubaian; Asma I. Alasqah (International Journal of Pediatrics)
Context. Studies about knowledge of emergency management of traumatic dental injuries (TDIs) which affect children by general dental practitioners (GDPs) and specialists in Saudi Arabia are lacking. Aim. The aim of this cross-sectional study was to assess the knowledge level of GDPs and specialists about TDI emergency management and its relation with demographic variables in Qassim region, Saudi Arabia. Materials and Methods. A random sample of 239 GDPs and specialists was given a two-part questionnaire; the first part included demographic questions and the second part included questions related to knowledge of emergency management of luxation (intrusion and extrusion), complicated crown fracture, and avulsion injuries. Data was statistically analyzed using chi-square and ordinal logistic regression tests. The significance was set at P<0.05. Results. The mean knowledge score was 5.57 for GDPs and 6.69 for specialists (out of 12). A significant difference was observed between both groups in the management of avulsion injury. Three factors significantly improved the dentists’ knowledge: gender (female), practice type (specialist), and previous experience of encountered TDIs (P<0.05). Conclusions. GDPs and specialists in Qassim region had moderate knowledge of emergency management of TDIs. Specialists were significantly more knowledgeable than GDPs in the management of avulsion injury when compared to the rest of the injuries.